Hydraulic analysis due to flooding in the Rimac river, Carapongo sector - Ricaldi, Eriksson Hipolito Pena (2023)
This article focuses on the simulation of the hydraulic behavior of the Rimac river in a 200-meter section in the Carapongo area of Lima, Peru, in order to determine the floodable areas in the event of increases in flows that exceed historical averages, calculating the levels of water and flow speeds to characterize the effects of flooding on the inhabitants who settle in nearby areas, as happened in March 2017 in the presence of flows of greater magnitudes in the Rimac river. [1] For the development of this article, the hydraulic simulation software called Hec Ras 6.2 was used using a fixed bed model with a fixed cross section channel, for which a topographic survey, granulometric analysis and subsequent estimation of the roughness coefficient were carried out, finally the review of the hydrological information with reference to the events that occurred in March 2017 in the Coastal Niño Phenomenon published in the technical reports of the National Meteorology and Hydrology Service of Peru (SENAMHI), for the consultation of the maximum flow data in March 2017 and estimation of the flow considering a flow of 200 m3/s; Finally, all this information was entered into the Hec Ras 6.2 software. The simulation results show us a flooded area near the San Antonio de Carapongo Wastewater Plant, with water depths reaching 1.0 m and a flow velocity of 5.0 m/s. The model was validated, making measurements of water depths in the field and verified with the values of simulated depth associated with the flows registered in the Chosica station of SENAMHI.